Nguci a New Musical Creations | Musik Kreasi Baru Nguci - Rata sunadi I Komang; I Wayan Suharta (GHURNITA: Jurnal Seni Karawitan, 2023)
This musical composition has the goal of expressing creativity and potential in art by creating quality and quality works of art. The work entitled tabuh kreasi “Nguci” is an innovative karawitan creation which is still based on Balinese karawitan traditional patterns. This work originated from the stylist's interest in the beauty of the sound of the pleci bird's song and has a cycle of sounds ranging from wheezing to ngalas, ngerol, ngeplong and gacor. So the stylist tries to transform it with a different character which will become a creation of percussion music with a tradition nuance. The process of creating this work goes through 5 stages, namely, the inspiration stage (ngawirasa), the exploration stage (ngawacak), the conception stage (ngaplan), the execution stage (ngewangun), the production stage (ngebah). This piece of percussion creation by Nguci consists of three parts, namely kawitan, pengawa and kecet. In its presentation, Nguci's percussion creations were played by 22 supporters with a duration of 12 minutes. The medium used to express this work of art is the gong angklung kebyar.